Mobile Architecture as Education Quality Enhancement of Street Children - Hasan Busri; FX Teddy Badai Samodra (IPTEK Journal of Proceedings Series, 2019)
Street children as a reality that can be found in every city in Indonesia becomes a "magnet" of urban issues especially in education sector. Marginal Theory assumes that urban poverty occurs due to culture of poverty that is isolated within certain societies with apathetic and pessimist individual characters and unsupportive family and community environments. The existence of marginalized groups became the main source of the occurrence of various forms of public illness, one of them is street children. Mobile Architecture is a reaction from the world of architecture in presenting new solutions in the social world. The phenomenon of formal education that is always seen with the size of formalities and measurable values, it should be seen from the other side that presents a reaction to the world of architecture as a container. The main question is how the concept of architectural flexibility can work optimally in the existence of this street children's school design? So that can be according to time, function and place. Architectural flexibility as the concept offered is accordance with current social and environmental conditions. This flexibility is supported by Portable Architecture and Folding Architecture methods so that a design - in this case street children’s school - can match the space at any time. This method allows to environment changes and can reach street children scattered at some point in the city. Based on the characteristics of street children who have demands on the street to make money, the empowerment approach proposed is the "Street Based Intervention" approach. This approach makes street children will be approached at a certain point then accommodated and given services in the form of education, coaching, and the place of play and socializing